Inhibition of radiographic progression in psoriatic arthritis by adalimumab independent of the control of clinical disease activity - Landewé, R; Ritchlin, C; Aletaha, D; Zhang, Y; Ganz, F; Hojnik, M; Coates, L (Oxford University Press, 2019)
Objectives To evaluate the relationship between radiographic progression and disease activity in subjects with PsA treated with adalimumab (ADA) or placebo (PBO) and the impact of concomitant MTX. Methods This was a post hoc analysis of the randomized, double-blind, PBO-controlled ADEPT trial. Subjects were categorized according to time-averaged (TA) disease activity (remission, low, moderate or high) based on Disease Activity Score of 28 joints with CRP [DAS28(CRP)], Disease Activity Index for Psoriatic Arthritis (DAPSA) or Psoriatic Arthritis Disease Activity Score (PASDAS), and achievement of minimal disease activity (MDA) at week 24. Radiographic progression was assessed as change in modified total Sharp score (ΔmTSS) from baseline to week 24. The analyses included interaction terms between disease activity and treatment on radiographic progression, comparison of radiographic progression in subjects categorized by disease activity and treatment, and correlation between disease activity and radiographic progression by treatment. Results The interaction terms for TA disease activity and treatment on ΔmTSS were significant (P = 0.002–0.008). Irrespective of concomitant MTX, ΔmTSS was lower with ADA vs PBO in all disease activity categories. Importantly, even in subjects having moderate or high disease activity or not achieving MDA, ΔmTSS was significantly lower on ADA than PBO (P = 0.05–0.001 for TA-DAPSA, TA-PASDAS and MDA). Correlations between TA disease activity scores and ΔmTSS were moderately positive and significant (P < 0.001) with PBO but non-significant with ADA. Conclusion Among subjects with PsA treated with ADA, there was evidence of a ‘disconnect’ between disease activity and radiographic progression: inhibition of radiographic progression was greater than expected based on control of clinical disease activity alone. MTX had no added effect.